2022
DOI: 10.1021/acs.iecr.2c01832
|View full text |Cite
|
Sign up to set email alerts
|

Toward Balanced Piezoelectric and Mechanical Performance: 3D Printed Polyvinylidene Fluoride/Carbon Nanotube Energy Harvester with Hierarchical Structure

Abstract: With rapid consumption of fossil energy and its impact on the environment, the desire for clean energy is gradually increasing around the world, and piezoelectric polymers have received extensive attention owing to their capability to harvest discrete mechanical energy in the environment. However, the existing piezoelectric devices are mostly low-dimensional fibers or films, making it difficult to achieve a good balance between mechanical robustness and piezoelectric output. Herein, a polyvinylidene fluoride (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Fused deposition modelling has attracted researchers' attention in the alternate energy domain such as energy harvesters. The MWCNT-polyvinylidene fluoride (PVDF)-based piezoelectric energy harvester, having a porous structure [85] and using heat during the printing, was printed. The studied method of foaming was reported to not affect the geometry parts.…”
Section: Carbon Nanotube Polymer Nanocompositementioning
confidence: 99%
See 1 more Smart Citation
“…Fused deposition modelling has attracted researchers' attention in the alternate energy domain such as energy harvesters. The MWCNT-polyvinylidene fluoride (PVDF)-based piezoelectric energy harvester, having a porous structure [85] and using heat during the printing, was printed. The studied method of foaming was reported to not affect the geometry parts.…”
Section: Carbon Nanotube Polymer Nanocompositementioning
confidence: 99%
“…A 1 wt% and 2 wt% nanocomposite's electronic image is shown in Figure 11b, detailing the dispersion of the nanoparticles in the polymer matrix phase. The authors demonstrated that the compressive strength increases from 509.09 kPa to 675.50 kPa for a 2 wt% nanocomposite energy harvester [85]. The dispersed nanoparticles behave as a stress conductor supporting the polymer matrix phase.…”
Section: Carbon Nanotube Polymer Nanocompositementioning
confidence: 99%
“…Improving piezoelectric properties of PVDF can be realized after addition of: conducting CB [267,268], CNTs [251,269,270], CNTs and G [134,271], GO [64,85,122,[272][273][274][275], CF [276], GO and polydopamine [229] G and GO with halloysite nanotubes [277], rGO [63,278],…”
Section: Practical Applications Of Pvdf-cnms In Various Generatorsmentioning
confidence: 99%